PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN PRASARANA LINGKUNGAN MELALUI PROGRAM DANA HIBAH KHUSUS (SUATU KAJIAN BANTUAN DANA PERDESAAN DI KECAMATAN KANDIS KABUPATEN SIAK) - Syaifuddin Syaifuddin; Sujianto Sujianto; Thamrin Thamrin (Jurnal Ilmu Lingkungan, 2013)
Participation of people in development of environment infrastructure through special grantprogram in Kecamatan Kandis, Siak Regency, correlation of people participation prior toimplementation, during implementation, and after implementation. The development shouldfulfill the requirement of regulation of Bupati Siak Nomor: 38 Year 2010. The data used inthe research is primary and secondary. The primary data was fulfilled by questionnaire topeople and stakeholders directly related to development of environment infrastructurethrough special grant program in Kecamatan Kandis, Siak Regency for 65 people that relatesto the variable of people participation and development of environment infrastructure thatare measured in Likert scale. Secondary data in the research was obtained from books andother information, from printed sources and other electronic source that relevance to theresearch. People participation in the village of Kandis, Sam-sam and Belutu in thedevelopment of environment infrastructure through special grant program in Kecamatan Kandis, Siak Regency was performed well. People participation in Kandis village was bettercompared to people participation in Sam-sam and Belutu village. Correlation of peopleparticipation in the village of Kandis, Sam-sam and Belutu prior, during, and after theimplementation of the development of environment infrastructure through special grantprogram in Kecamatan Kandis, Siak Regency has significant influence. People participation before and after the development partially influence the development of environmentinfrastructure. However, people participation during the implementation did not has influence because the development still in progress according to program planning althoughthere was no people participation during the development. The development of environmentinfrastructure through special grant program in Kecamatan Kandis, Siak Regency has beenperformed well and has fulfilled the requirement of regulation of Bupati Siak Nomor: 38 Year 2010, which are effective, correct time, correct amount, and in good quality.